Why and Where We Choose to Treat Children with Intravenous Antibiotic for Febrile Urinary Tract Infection/Pyelonephritis. (4th October 2017) - Scanlan, Barry; Ibrahim, Laila; Hopper, Sandy; Babl, Franz; Davidson, Andrew; Bryant, Penelope
Abstract: Background: Febrile UTI/pyelonephritis is a common diagnosis for children presenting to the Emergency Department (ED). A Cochrane review of the management of pyelonephritis in children showed no difference between intravenous (IV) and oral antibiotics. Despite this, many children are treated with at least initial IV antibiotics. The reasons are often unclear and it is uncertain whether this is appropriate as the Cochrane review excluded children at the worse end of the clinical spectrum. Our aim was to determine why physicians made these decisions as a first step in determining whether this is necessary. Methods: A prospective observational study of children presenting to the ED at the Royal Children's Hospital with UTI/pyelonephritis from Oct 2016 – Apr 2017. Data collection included demographic, clinical features, microbiology, treatment and outcomes. ED physicians were asked to record reasons for prescribing IV antibiotics and for treating the patient in hospital vs. in hospital-in-the-home (HITH). Results: 170 children were included, 123 (72%) were treated with oral antibiotics, 43 (25%) IV and 4 (3%) intramuscular – these are now included in the IV group. In the IV group, 32 (19%) were admitted, 3 (2%) were transferred directly to HITH from ED and 13 had a single dose of IV antibiotics in ED and were discharged. A comparison of the clinically significant features between the two groups is outlined (Table 1). The commonest reasons cited for using IV antibiotics and for hospital admission vs. HITH is shown (fig 1 and 2). Conclusion: This is the first study of decision-making for IV antibiotics and hospital admission for UTI/pyelonephritis in children. The fact that the reasons cited for IV antibiotics were often not evident on objective clinical data suggests that there may be overuse of IV antibiotics. We will present an assessment of appropriateness and suggest alternatives to the traditional IV and hospital admission route. Disclosures: All authors: No reported disclosures.